Distribution of volumes of plasma channels components between metal granules in working liquids - N. A. Shydlovska; S. M. Zakharchenko; M. F. Zakharchenko; M. A. Kulida; S. A. Zakusilo; R. A. Yakovenko (Electrical engineering & Electromechanics)
Introduction. Expanding the capabilities of a number of modern technologies and improving quality of their products require detailed spark and plasma erosion processes control in metal granules layers (MGL). Problem. Traditional measurement of exclusively electrical parameters of these processes, even in the case of multi-electrode systems, provides only a general vision, not allowing monitoring processes in individual plasma channels. Optical control methods make it possible to simultaneously have information about almost every plasma channel in the MGL. The aim of the article is to study the characteristic components of plasma channels arising as a result of the flow of discharge currents in the MGL and to establish the laws of distribution of their volumes and their ratios. Methodology. During the experiments, photographs of plasma channels resulting from the flow of discharge current pulses between Al granules immersed in distilled water were obtained. Using the specialized ToupView program, the volumes of equivalent ellipsoids of rotation, approximating the colored halos and white cores of the plasma channels were determined. Discrete distributions of the volumes of the halo and cores of plasma channels, as well as their ratios were constructed both with and without procedures for screening out «anomalous» results. The efficiency of approximation of discrete distributions obtained in practice by continuous theoretical distributions Weibull, Rosin-Rammler and log-normal was estimated. Results. It is shown that of all the considered theoretical distributions of halo and cores of plasma channels volumes, as well as their ratios, the most adequate is the log-normal one. Originality. For the first time distributions of volumes of halo and cores of plasma channels were studied and their comparative analysis with the size distributions of erosion particles and dimples on the surface of Al granules was given. Practical significance. Taking into account the new obtained results, a technique for constructing distributions of volumes of halo and cores of plasma channels and determining their parameters has been developed. References 53, figures 7, tables 5.